Elementy demokracji deliberacyjnej jako sposób na zwiększenie partycypacji obywateli w polskim życiu publicznym - Goworek, Katarzyna (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2017)
The participation of citizens in public life, also via deliberation has a positive influence on development of civil society and democracy. citizens’ participation in decision making process increase their influence on important issues of their state. wide consultations let authorities to recognize public problems and solve them in an effective way. however, it is necessary to engage both – citizens and authorities – to provide a proper deliberation development. authorities should create more possibilities for deliberation. accomplishing the consensus is not always possible but it is important to make it possible for every citizen to express their opinion, not only during the elections. the development of new media and the internet promotes deliberation and allows the insight into the public opinion.